(untitled) (Medical Forum Monthly, 2021)
Objective: The study's main aim is to look at the occurrence of the coronary artery disease in adults based upon their sleep duration. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at the Wah Medical College located at Wah Cantt, also Gomal Medical College in D.I. Khan January, 2018, to December, 2018. Materials and Methods: The research included about 400 of the patients with coronary artery disease who were 18 to 65 years old and of either sexual orientation. The patients' average age was 48.96 12.5 years, with a range of 18 to 65 years. 277 (69.25 percent) of the 400 patients were men, while 123 (30.75 percent) were women. Results: The average BMI of the people in the study was 29.27 4.42 kg/m2. 45.75 percent of patients had a BMI of less than 27.5 kg/m2, while 54.25 percent had a BMI of more than 27.5 kg/m2. 234 (58.5%) of the people in the study had diabetes, 189 (46.23%) have high blood pressure (hypertension), 229 (56.24%) smoke, 243 (60.70%) have dyslipidemia and about 238 of the people (59.5%) are diagnose with coronary artery disease family background. This study supposed that the recurrence of CAD in adults who slept for less than six hours and over eight hours was more prevalent. Conclusion: Research suggests that coronary artery disease recurrence is more common for adults who have slept for less than six hours and 8 hours. We therefore propose coordination at the community level of educational programmes to teach individuals how to sleep (6-eight hours), in order to lower the danger of coronary artery conditions.